2006
DOI: 10.1002/anie.200504386
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Activity of Electrocatalysts for Oxygen Reduction by Tuning the Surface Electronic Structure

Abstract: The fuel cell is a promising alternative to environmentally unfriendly devices that are currently powered by fossil fuels. In the polymer electrolyte membrane fuel cell (PEMFC), the main fuel is hydrogen, which through its reaction with oxygen produces electricity with water as the only by-product. To make PEMFCs economically viable, there are several problems that should be solved; the main one is to find more effective catalysts than Pt for the oxygen reduction reaction (ORR), 1/2 O 2 + 2 H + + 2 e À = H 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

75
1,416
2
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,812 publications
(1,503 citation statements)
references
References 35 publications
75
1,416
2
10
Order By: Relevance
“…They concluded that late transition metal atoms with low coordination numbers (i.e., having open surfaces, steps, edges, kinks and corners) tend to have higher d-states and therefore interact more strongly with adsorbates than do the atoms on close-packed surfaces with high metal coordination numbers. This theory, which has been experimentally validated by Stamenkovic et al 34 and successfully applied in the search for ORR catalysts more effective than Pt, shows that Pt-alloys involving 3d metals are better catalysts than Pt because the electronic structure of Pt atoms on the surface of Pt-alloys has been slightly modified. Stamenkovic et al developed a series of well-characterized alloys that showed interesting volcano-shaped variations in electrocatalytic activity, and provided a starting point for developing and understanding the factors that control ORR kinetics.…”
Section: Ms Lei Zhang Is a Researchmentioning
confidence: 78%
See 1 more Smart Citation
“…They concluded that late transition metal atoms with low coordination numbers (i.e., having open surfaces, steps, edges, kinks and corners) tend to have higher d-states and therefore interact more strongly with adsorbates than do the atoms on close-packed surfaces with high metal coordination numbers. This theory, which has been experimentally validated by Stamenkovic et al 34 and successfully applied in the search for ORR catalysts more effective than Pt, shows that Pt-alloys involving 3d metals are better catalysts than Pt because the electronic structure of Pt atoms on the surface of Pt-alloys has been slightly modified. Stamenkovic et al developed a series of well-characterized alloys that showed interesting volcano-shaped variations in electrocatalytic activity, and provided a starting point for developing and understanding the factors that control ORR kinetics.…”
Section: Ms Lei Zhang Is a Researchmentioning
confidence: 78%
“…55 Stability testing of Pt 3 M alloys in a vacuum (M = Ir, Co, Ni and Fe) showed that Pt 3 Ir(111) > Pt 3 Co(111) > Pt 3 Ni(111) > Pt 3 Fe(111). 6 Stamenkovic et al 34 studied polycrystalline alloy films of Pt 3 M catalysts (M = Ni, Co, Fe and Ti) to understand the role of 3d metals in the electrocatalytic ORR activity of Pt-alloys. They found that in these Pt 3 M alloys, the first outlayer was enriched by Pt due to surface segregation.…”
Section: Effects Of Compositionmentioning
confidence: 99%
“…12 We also studied O 2 dissociation on Pt(111) and a Pt-skin layer on Pt 3 Ni, and a similar trend (0.71 eV on Pt(111) vs 0.97 eV on the Pt-skin) was found. 51,74 On the other hand, adsorption of CO, H, O, and O 2 on Pt-skin surfaces is weakened by the subsurface TMs, 9,10,32,[51][52][53]60 but the destabilization occurs with a similar magnitude. 44,51 For example, binding energies of CO and O 2 on a Pt-skin with subsurface Ru are -1.25 and -0.26 eV, respectively, compared to -1.82 eV/CO and -0.65 eV/O 2 on Pt(111).…”
Section: ' Introductionmentioning
confidence: 99%
“…Oxygen reduction electrocatalysts are known to play a crucial role on fuel cells performance, being the fundamental studies on the subject still required to overcome these barriers 3,4 . By alloying Pt with other non-noble metals, it is possible to produce cheaper electrocatalysts with novel properties for the oxygen reduction reaction (ORR) due to lattice compression 5,6 and/or modified electronic properties 7,8 . Thus, several studies have shown that binary Pt-M (M=Cr, Mn, Fe, Co, Ni, Cu, V, Ti) nanocrystals (NCs) greatly enhanced the kinetics of the ORR in comparison with standard Pt catalysts [9][10][11] .…”
mentioning
confidence: 99%